Maurizio Moro: «Imagine del Salvatore dal Pordenon Pittor famoso dipinta».: Un componimento ritrovato per un dipinto perduto - BORTONE, MILENA (Italianistica Debreceniensis, 2021)
In the essay Note sulla tradizione spirituale e religiosa Quondam denounced the prejudice which for a long time excluded from the field of “literature” the experiences of religious poetry of the pre-baroque era. The issue is greater in the field of figurative arts, where sacred poetry and those who dealt with it still find it hard to establish themselves as sources for the knowledge of works and artistic languages. This is the case of the Venetian Maurizio Moro, a canon and scholar who lived between the 16th and 17th centuries, known above all as the author of the commentary verses on Dürer’s Little Passion (Venice, 1612). The essay discusses the author’s composition on the «Imagine del Salvatore, dal Pordenon pittor famoso dipinta». The text, published in 1609 within the Amorosi stimoli dell’anima penitente and still unknown to those who have treated the Friulan painter, bears witness to a work not otherwise known, re-evaluating Moro as a precious source for art history and criticism.